Child and adolescent emotional state affected by winter - Bravo García, Leslie Yuliet (2016)
Columbia suffered a strong winter season during 2010 and part of 2011, as a result of the “La Niña” Phenomenon. Thus, in attempt to describe the emotional state of children and adolescents affected by the harsh winter of 2011 in the Sub Regions Mojana and San Jorge from the department of Sucre, a sample of 406 children and adolescents, aged between 10 and 14 years, were studied. The methodology used was descriptive and utilized a positivist paradigm, finding that the children and adolescents did not possess sufficient defenses in order to adapt to the environment, 88% in Mojana and 95% in San Jorge, which suggests a prompt intervention in infancy and adolescence affected by climate change.